Tafsir Post-Kolonial Femenis Yehezkiel 16:15-22 sebagai Teks Pornografi Kenabian - Yohanes Parihala; Jelfy L Hursepuny (UIN Sunan Gunung Djati Bandung, 2020)
The issue of violence against women not only occurs in the space of action or the form of direct violence but also in the way of indirect violence, among others through the understanding of the biblical text that discredit women. This study aims to carry out a postcolonial feminist interpretation of Ezekiel 16: 15-22. This text, if understood, literally contains pornographic ideological messages that confront women as victims. Qualitatively, the interpretative analysis approach helps the writer to reinterpret the meaning of Ezekiel 16: 15-22 and find its relevance to the feminist struggle in the present. For this reason, the study of literature is the choice of writing to study various references related to the issues discussed. The results of this study indicate that certain Bible texts written in a patriarchal context have a picture of discrimination against women. With the feminist postcolonial approach, the reinterpretation of discriminatory texts can be done by emphasizing that both men and women were created equally by God.